2008
DOI: 10.1002/clc.20221
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Simple Versus Complex Stenting of Coronary Artery Bifurcation Lesions in Daily Practice in Chinese Patients

Abstract: Background: Recently, several randomized and controlled trials have demonstrated great advantages of a drug-eluting stent (DES) with respect to significant reduction in restenosis and recurrence of symptoms, and improvement in clinical outcomes after percutaneous coronary intervention (PCI). Little is known about the comparative effects of the 1-DES plus the kissing balloon technique with the 2-DES for bifurcation angioplasty in a Chinese population. Methods: From April 2004 to June 2006, 566 consecutive Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
1
7
1
Order By: Relevance
“…Thus, the provisional stenting strategy was safer than the complex strategy that was associated with higher incidence of in-hospital and 9-month major adverse cardiovascular events, mainly contributed to by periprocedural myocardial infarction. Results of our study were in agreement with that reported in Gao et al [24]: 566 patients with significant coronary bifurcation lesions were randomized to a simple or complex stenting strategy, using drug-eluting stents. In the simple stenting strategy, the main branch was stented, with mandatory side branch kissing balloon dilatation (i.e., single-stent strategy).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the provisional stenting strategy was safer than the complex strategy that was associated with higher incidence of in-hospital and 9-month major adverse cardiovascular events, mainly contributed to by periprocedural myocardial infarction. Results of our study were in agreement with that reported in Gao et al [24]: 566 patients with significant coronary bifurcation lesions were randomized to a simple or complex stenting strategy, using drug-eluting stents. In the simple stenting strategy, the main branch was stented, with mandatory side branch kissing balloon dilatation (i.e., single-stent strategy).…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, the initial remarkable acute gain after SB stenting was partly offset by the late loss. Nevertheless, wider SB ostium at the time of follow-up coronary angiography was demonstrated in the two-stent group, even thought the late loss was larger than previous studies ( 17 , 18 ). In addition, more favorable diameter stenosis was proven, too.…”
Section: Discussioncontrasting
confidence: 66%
“…These findings suggest that the 1-stent technique might be less affected by bifurcation angle, since the change in vessel geometry is relatively small after stent implantation. Bifurcation angle might be a less important factor in predicting clinical outcome in the real world, where a simple strategy would be preferable to a systemic 2-stent strategy [10,11,12,13]. …”
Section: Discussionmentioning
confidence: 99%